2012
DOI: 10.1183/09059180.00008111
|View full text |Cite
|
Sign up to set email alerts
|

Repeated cross-sectional survey of patient-reported asthma control in Europe in the past 5 years

Abstract: Although the main goal of asthma management guidelines is to achieve and maintain clinical control, reported levels of not well-controlled asthma remain high. The aim of this analysis was to compare the levels of asthma control and the associated impact on patients' health status in Europe in 2006, 2008 and 2010. An additional outcome was the comparison of the burden of asthma with diabetes. Data were obtained from the cross-sectional, self-reported, European National Health and Wellness Surveys conducted in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
157
2
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(187 citation statements)
references
References 35 publications
14
157
2
14
Order By: Relevance
“…The general attitude of Albanian asthmatics shows a similarity towards Europeans with severe BA in the industrialized countries [2][3][4][5][6][7][8][9][10][11]. These findings suggest that in our country patients with uncontrolled asthma represent the majority, and that Albanian (predominantly male) patients consider their BA as a disease only if they experience uncontrolled symptoms and daily restrictions.…”
Section: ) Opinion Of Albanian Asthmatics Over the Next Five Yearsmentioning
confidence: 66%
See 2 more Smart Citations
“…The general attitude of Albanian asthmatics shows a similarity towards Europeans with severe BA in the industrialized countries [2][3][4][5][6][7][8][9][10][11]. These findings suggest that in our country patients with uncontrolled asthma represent the majority, and that Albanian (predominantly male) patients consider their BA as a disease only if they experience uncontrolled symptoms and daily restrictions.…”
Section: ) Opinion Of Albanian Asthmatics Over the Next Five Yearsmentioning
confidence: 66%
“…This demonstrate that a substantial proportion of asthmatics remain not well-controlled [8]. In 2010, the proportion of treated asthma patients assessed as having not well-controlled asthma was about 54%, compared to 57% and 55% in 2008 and 2006, respectively [2,8].…”
Section: ) Opinion Of Albanian Asthmatics Over the Next Five Yearsmentioning
confidence: 93%
See 1 more Smart Citation
“…1 The International Study of Asthma and Allergies in Childhood (ISAAC) reported that there was a high proportion of children with asthma symptoms in several low-and middlei ncome countries, and that the prevalence of asthma is increasing in some of these countries. 1,2 Unfortunately, management of asthma is suboptimal for a substantial proportion of asthma patients worldwide, [3][4][5] and most have limited access to affordable inhaled corticosteroids. [6][7][8] A comprehensive lung health project funded by the World Bank and implemented through collaboration between the International Union Against Tuberculosis and Lung Disease (The Union) and partners in Benin, China and Sudan, included as one of its aims to reduce the burden of lung disease through improvement of case management of patients with persistent asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The economic burden in terms of direct (hospitalization, use of emergency room visits, therapy) and indirect (missed days of work/school) costs adds to the emotional, physical and social impact of asthma, with consequent quality of life deterioration for both patients and their families [3]. Despite the availability of effective treatments, a large proportion of asthma patients experience symptoms of uncontrolled asthma, even in those geographical areas where good standards of care are available [2,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%